Determinants of Male Partner Involvement in Utilization of Family Planning Methods: A Mixed Methods Study - Pushpa Omprakash Lokare; Ajinkya Deshmukh; Amruta Bavadekar; Vinod Deorao Karanjekar; Sanjeev Mohan Chaudhary (Journal of Integrated Health Sciences)
Introduction: Despite many efforts to promote gender equality in reproductive health, there has been minimal progress in reducing the gap between men’s and women’s contraceptive utilization. Men should become equal partner of women by overcoming social and cultural barriers in family planning and support women’s contraceptive choices. The present study investigated the determinants of male partner involvement in family planning (FP) services. Aims: The aim of this study was to know the various determinants of male partner involvement in the utilization of FP methods and understand the barriers in acceptance of FP methods by male partner. Material and Methods: A mixed methods study was conducted among 315 male participants over a period of 12 months from September 2022 to August 2023. Results: The male partner involvement was found to be 66% in the present study. Factors such as occupation of spouse, number living daughter, number of contraceptives known, knowledge of FP clinic, knowledge of spacing interval, and ever communicated with spouse on contraceptives were found strong determinants with male partner involvement utilisation of family planning methods on regression analysis. Cultural and religious factors were significantly related since some respondents stated that it is against their religion to use contraceptives. Conclusion: Misconceptions, especially about vasectomies, were widespread and caused low uptake. Societal norms favored family planning as solely a woman’s responsibility. The findings suggest that sensitization of healthcare providers and specific educational interventions are needed to encourage male involvement.